2017
DOI: 10.1161/atvbaha.116.308502
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish Model for Functional Screening of Flow-Responsive Genes

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 50 publications
8
52
0
Order By: Relevance
“…Our work complements previous work (Serbanovic-Canic et al, 2017) which found blood flow cessation to induce EC apoptosis in zebrafish embryos at 30hpf, while our assessment of cerebral microglia numbers extends the examinations of Xu et al who limited their studies to microglia of the tectum (Xu et al, 2016). Our finding that NO is lacking in the bulbus arteriosus at 3dpf in fish without blood flow is the first functional evidence of bulbus arteriosus NO to be blood flow dependent (Grimes et al, 2006).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our work complements previous work (Serbanovic-Canic et al, 2017) which found blood flow cessation to induce EC apoptosis in zebrafish embryos at 30hpf, while our assessment of cerebral microglia numbers extends the examinations of Xu et al who limited their studies to microglia of the tectum (Xu et al, 2016). Our finding that NO is lacking in the bulbus arteriosus at 3dpf in fish without blood flow is the first functional evidence of bulbus arteriosus NO to be blood flow dependent (Grimes et al, 2006).…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, control morpholino group account for injection-induced developmental delays (Stainier et al, 2017). Previous studies used this method to study the impact of blood flow on specific cerebral (Fortuna et al, 2015;Rödel Claudia Jasmin et al, 2019) and trunk vessels (Watson et al, 2013), showing reduced trunk EC numbers when blood flow is absent (Serbanovic-Canic et al, 2017;Watson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that the Wnt pathway may be regulated by mechanical forces, although they may also be increased secondary to other mechanically activated pathways. Interestingly, the expression of Lrp6 is increased in cells exposed to uniform flow (65) suggesting that different Wnt pathways may be active under different flow conditions. Nuclear accumulation of β-catenin has also been observed in an atheroprone region of the mouse aorta, in the absence of lesions, suggesting flow-dependent regulation.…”
Section: Mechanical Regulation Of Wnt Signalling In the Vasculaturementioning
confidence: 99%
“…Given the different effects of Jag1 and Dll4 on atherosclerosis, we hypothesised that Notch receptors and ligands may have a different spatial pattern of expression in arteries. This was tested by qRT-PCR analysis of transcripts of Notch receptors and their ligands isolated from regions of the porcine aorta exposed to LOSS (inner curvature) or HSS (outer curvature) using a shear stress map generated previously by our group 16 . The expression of JAG1 and NOTCH4 mRNA was significantly enhanced at sites of LOSS compared to HSS whereas the expression of DLL4, NOTCH1, NOTCH2 and NOTCH3 was similar between these sites ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Data are presented as means values ± SEM. Statistical analysis were performed with 16 . Based on this map, endothelial cells were specifically isolated from LOSS area versus HSS area in the porcine aortic arch.…”
Section: Resultsmentioning
confidence: 99%